Le giardiniere. Semi, radici, propaggini dall'Inghilterra al mondo - Orestano, Francesca; Rudelli, Anna; Zappatini, Anna (Milano University Press, 2021)
Gardeners are all those women who, from the eighteenth century to the present day, have worked in the garden, planting, pruning, selecting, illustrating, and becoming involved in the production of gardening texts, scientific and botanical research, the design of green spaces, and movements for the protection of the landscape. From England, where the passion for horticulture has a well-documented history, women protagonists in the history of the garden have travelled to America, Australia, New Zealand and Asia, crossing the borders of our old world but always carrying with them their roots, replanted in distant lands. Francesca Orestano, Anna Rudelli and Anna Zappatini have outlined these adventurous stories, and the lessons that can be learnt from them, even by growing a simple geranium on the window sill.